PEMANFAATAN JB CLASS UNTUK MENDORONG KEMANDIRIAN BELAJAR SISWA DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Arif Kurniawan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2020)
Self-regulated learning is very important during online learning in Covid-19 pandemic, since there is no face to face interaction between teacher and students. However, this student ability has not been found in our online class of Biology in X MIPA 1. Based on the author's reflection, students are still very dependent on teacher instruction during their learning activities. To overcome this problem, the author applied online learning utilizing JB Class by implementing self-regulated learning strategies adapted from Wandler & Imbriale (2017). Result of the study describes that online learning using JB Class is able to encourage student’s self-regulated learning. Based on the questionnaire filled out by students, the self-regulated learning among students of class X MIPA 1 reaches 75%.